ESTRATEGIES TO PROMOTE RESEARCHIN THE CLASSROOM - Inga Arias, Miguel Gerardo (2014)
This article presents strategies on how to promote research from the classroom and in the classroom. It also adds how it is possible to promote internal motivation which will generate a cognitive conflict, as well as how to manage information in search of answers to proposed problems. This work also contemplates the formulation of hypothesis, the managing of the information and the operation of variables.